2011
DOI: 10.1152/ajpgi.00108.2011
|View full text |Cite
|
Sign up to set email alerts
|

Expression, localization, and functional role for synaptotagmins in pancreatic acinar cells

Abstract: induced changes in intracellular Ca 2ϩ play a pivotal role in secretion in pancreatic acini yet the molecules that respond to Ca 2ϩ are uncertain. Zymogen granule (ZG) exocytosis is regulated by soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complexes. In nerve and endocrine cells, Ca 2ϩ -stimulated exocytosis is regulated by the SNARE-associated family of proteins termed synaptotagmins. This study examined a potential role for synaptotagmins in acinar secretion. RT-PCR revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…We previously identified a potential role for the Ca 2ϩ -sensing regulatory protein syt1 in VAMP2-mediated exocytosis (43). Analysis of VAMP2 in whole cell lysates revealed a 4-fold increase in VAMP8 Ϫ/Ϫ acini consistent with the increased numbers of ZGs (Fig.…”
Section: (42) Vamp8mentioning
confidence: 69%
“…We previously identified a potential role for the Ca 2ϩ -sensing regulatory protein syt1 in VAMP2-mediated exocytosis (43). Analysis of VAMP2 in whole cell lysates revealed a 4-fold increase in VAMP8 Ϫ/Ϫ acini consistent with the increased numbers of ZGs (Fig.…”
Section: (42) Vamp8mentioning
confidence: 69%
“…Following 2-min CCK-8 stimulation, D52 was present along the cytoplasmic edge of actin filaments, but absent from the apical membrane. Previous studies using various antibodies have demonstrated that VAMP2-positive ZGs are present within the most apical aspects of the acinar cytoplasm (7,19,20,73) and rapidly accumulate within apical actin filaments and on apical plasma membranes following CCK-8 stimulation (73). In stimulated cells, D52 showed only minimal colocalization with VAMP2 in areas confined to the cytoplasmic side of actin filaments (Fig.…”
Section: D52 Is Present Within Apical Endolysosomal Compartments In Amentioning
confidence: 82%
“…We previously demonstrated that ZG exocytosis can be analyzed in acinar cell whole preparations by surface labeling with an antibody that recognizes the ZG luminal domain of syt1 (see Fig. 5D), which is externalized upon acinar stimulation and ZG exocytosis (20). Analysis of CCK-8-stimulated acini viewed in a reconstructed 3D format shows incomplete overlap of the syt1-and LAMP1-associated fluorophores in apical regions of acini (Fig.…”
Section: G445mentioning
confidence: 89%
“…Furthermore, there is evidence that this mechanism may be universally conserved, since 4 isoforms have been identified for complexin and sytI belongs to a family of 16 members that are expressed in several secretory tissues [5]. Indeed, SytI has been shown to play a role in the exocytosis of zymogen granules in the pancreas and dense core vesicles in the adrenal medulla [143], whereas sytII, V, VII and IX have been reported to regulate the exocytosis of Glut 4 vesicles [144, 145] and secretory granules in mast and NK cells [146, 147]. …”
Section: Regulated Exocytosismentioning
confidence: 99%